Optimizing the Role of the Indonesian Waqf Board of North Sumatra Province in Increasing the Professionalism of Nazhir in Managing Waqf Productively in Medan Marelan District, Medan City - Ichwanul Qawi; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study aims to examine the optimization of the role of the Indonesian Waqf Board (BWI) of North Sumatra Province in improving the professionalism of waqf managers (nazhir) in managing productive waqf in Medan Marelan District. The background of this research is based on the fact that waqf management is still predominantly traditional and consumptive, which limits its potential as an instrument for socio-economic empowerment. This study employs a qualitative method with an empirical juridical approach, analyzing law not only as a set of norms but also as it is implemented in practice. Data were collected through interviews with representatives of BWI North Sumatra and local nazhir, supported by a literature review of relevant laws and academic sources. The findings indicate that the professionalism of nazhir remains relatively low, particularly in terms of managerial skills, administrative capacity, and understanding of productive waqf concepts. Furthermore, the role of BWI North Sumatra in guiding and supervising nazhir has not been fully optimized due to limited resources, insufficient training programs, and uneven distribution of capacity-building initiatives. As a result, the development of productive waqf management in the research area has not yet been achieved. Therefore, strengthening the role of BWI through intensive training, continuous mentoring, and improved supervision mechanisms is essential to enhance nazhir professionalism and to maximize the economic benefits of waqf for the community